Development and Effectiveness Verification of an Online Career Adaptability Program for Undergraduate Students - Kim, Jihyo (Frontiers in Psychology, 2022)
This study developed an online career adaptability improvement program as part of the undergraduate curriculum to improve college students’ career adaptability and verify its effectiveness. This 13-week intervention program, developed using the Korea-Career Adaptability Scale (K-CAS), consists of three domains: 1) knowledge and recognition of the self and work environment, 2) self-directed coping related to career behavior, and 3) environmental interaction for career decisions and adaptation. Two sub-studies were conducted to achieve the research objectives: Study 1 included developing and testing a pilot program and Study 2 quantitatively analyzed the final program to test its effectiveness. In Study1, preliminary program development and validity were verified, and in Study2, the effectiveness of the final program was verified. As a strategy to achieve the research purpose, in Study1, literature review and needs analysis, program design reflecting the results of the needs analysis, validity verification through Delphi survey, preliminary program implementation and evaluation, and the operation of the final program were performed. To test the effectiveness of the program in Study 2, a pre-posttest of career adaptability was conducted on experimental (n = 54), comparison (n = 56), and control groups (n = 53) using the non-equivalent group pretest-posttest design, followed by a program satisfaction survey. This study is meaningful in that it developed an online program to help college students improve career adaptability and identified its effectiveness. This study yielded two results. First, it successfully developed a career adaptability improvement program for undergraduate students, wherein the career development tasks, and the sub-factors of career adaptability were organically interlinked. Second, it verified the statistically significant differences in the career adaptability scores among the experimental, comparison, and control groups. The highest mean score was obtained by participants in the experimental group, followed by the comparison and the control group.